Release of Mps1 from kinetochores is crucial for timely anaphase onset - Jelluma, Nannette (The Rockefeller University Press, 2010)
Mps1 kinase activity is required for proper chromosome segregation during mitosis through its involvements in microtubule–chromosome attachment error correction and the mitotic checkpoint. Mps1 dynamically exchanges on unattached kinetochores but is largely removed from kinetochores in metaphase. Here we show that Mps1 promotes its own turnover at kinetochores and that removal of Mps1 upon chromosome biorientation is a prerequisite for mitotic checkpoint silencing. Inhibition of Mps1 activity increases its half-time of recovery at unattached kinetochores and causes accumulation of Mps1 protein at these sites. Strikingly, preventing dissociation of active Mps1 from kinetochores delays anaphase onset despite normal chromosome attachment and alignment, and high interkinetochore tension. This delay is marked by continued recruitment of Mad1 and Mad2 to bioriented chromosomes and is attenuated by Mad2 depletion, indicating chronic engagement of the mitotic checkpoint in metaphase. We propose that release of Mps1 from kinetochores is essential for mitotic checkpoint silencing and a fast metaphase-to-anaphase transition.